Exploring Porphyrins, Phthalocyanines and Corroles as Photocatalysts for Organic Transformations - Jain, Ashmita; Gupta, Iti (SynOpen, 2024)
In recent years, macrocycles have emerged as efficient and sustainable photosensitizers for the catalysis of organic transformations. This graphical review provides a concise overview of photocatalysis and photoredox catalysis utilizing three common macrocycles: porphyrins, phthalocyanines and corroles. They exhibit strong absorption in the visible region and can be easily oxidized or reduced, making them good candidates for photocatalysis.
Keywords: photocatalysis; photoredox catalysis; porphyrins; phthalocyanines; corroles